1985
DOI: 10.2307/1367139
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Olfactory Detection of Food Caches by Black-Billed Magpies

Abstract: Although the importance of olfaction in birds is being increasingly recognized, its role in species with very small olfactory bulbs, such as corvids, is largely unknown. In field experiments designed to examine whether Black-billed Magpies (Pica pica) use olfaction to locate hidden food, we found that magpies uncovered significantly more caches of suet and raisins scented with cod liver oil than control caches. We suggest that in recovering caches, magpies use a multicue system that may involve both memory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…Subsequent controlled observations and more extensive studies under natural conditions at sea provided support for Collins' and other early field reports, confirming the attraction of procellariiforms to different odours directly linked to food, such as cod liver oil, krill and squid homogenates (Grubb, 1972;Hutchison and Wenzel, 1980;Hutchison et al, 1984;Jouventin and Robin, 1984;Lequette et al, 1989;Nevitt, 1999b;Nevitt et al, 2004;Verheyden and Jouventin, 1994). The use of olfaction to locate food has also been revealed in terrestrial environments by turkey vultures, kiwis, magpies and honeyguides (Buitron and Nuechterlein, 1985;Stager, 1964;Stager, 1967;Wenzel, 1971). More generally, odours are an essential component of navigation over land in homing pigeons, starlings, swifts and catbirds (Fiaschi et al, 1974;Holland et al, 2009;Papi, 1989;Wallraff et al, 1995).…”
Section: Introductionmentioning
confidence: 57%
“…Subsequent controlled observations and more extensive studies under natural conditions at sea provided support for Collins' and other early field reports, confirming the attraction of procellariiforms to different odours directly linked to food, such as cod liver oil, krill and squid homogenates (Grubb, 1972;Hutchison and Wenzel, 1980;Hutchison et al, 1984;Jouventin and Robin, 1984;Lequette et al, 1989;Nevitt, 1999b;Nevitt et al, 2004;Verheyden and Jouventin, 1994). The use of olfaction to locate food has also been revealed in terrestrial environments by turkey vultures, kiwis, magpies and honeyguides (Buitron and Nuechterlein, 1985;Stager, 1964;Stager, 1967;Wenzel, 1971). More generally, odours are an essential component of navigation over land in homing pigeons, starlings, swifts and catbirds (Fiaschi et al, 1974;Holland et al, 2009;Papi, 1989;Wallraff et al, 1995).…”
Section: Introductionmentioning
confidence: 57%
“…However, the kiwi does have the largest ratio of diameter of olfactory bulb to diameter of cerebrum of any bird (Bang & Cobb, ). An experimental study on the olfaction capabilities of corvids, which have a small olfactory bulb to cerebrum ratio (~6%, Bang & Cobb, ), showed that they could readily locate cached food via smell in the absence of visual cues (Buitron & Nuechterlein, ). Another study examined the number of olfactory receptor (OR) genes in nine bird species across seven orders and found that the total number of OR genes correlates positively with relative olfactory bulb size (measured as in Bang & Cobb, ; Steiger et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, their attention might have been focused only towards visual cues to the cache site, such as changes in the substrate's consistency. Olfactory cues might also have been used (Buitron & Nuechterlein 1985;Harriman & Berger 1986). We aimed to determine whether ravens could find food caches more accurately after observing conspecifics during caching than when they had observed conspecifics only manipulating food and starting caching attempts in a given area, but could not see the final caching events.…”
Section: Observational Learning Of Cache Locationmentioning
confidence: 99%